Evaluating the Government Hospitals’ Efficiency and Their Impact on Human Development in Iraq - Hasan Jabur , Wafaa; Abdul Manaf Raheem, Luma ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Actually, hospitals are considered most important and prominent healthcare institutions providing healthcare services. They are the cornerstone upon which a city relies to obtain these services, as they care for people’s health and psychological well-being, enabling them to perform their duties effectively. They also provide all medical and consulting specialties. Given their importance, they are located in an urban area that is a convenient location to ensure accessibility for residents, as well as ensuring access to all their treatment and hospitalization needs. The current study aims to examine the reality of healthcare services in terms of number and geographical distribution, achieving balanced growth between the number of government hospitals and healthcare personnel on the one hand, and the quality of healthcare services on the other. It also aims to achieve human and health development to meet the community’s needs for health services, both quantitatively and qualitatively. The study has found that the highest percentage of government hospitals was concentrated in the Iraqi capital (Baghdad), with (35) hospitals, including (9,297) doctors with various specialties. This was in addition to the unfair distribution of government hospitals among the Iraqi governorates, with Muthanna and Kirkuk governorates recording the lowest number of government hospitals